The Reallocation of Workers and Jobs in Russian Industry: New Evidence on Measures and Determinants - J. David Brown; John S. Earle (Institute for the Study of Labor (IZA), 2002)
Gross job and worker flows in Russian industry are studied using panel data from a recent survey of 530 firms selected through national probability sampling. The data permit an examination of several important measurement issues – including the timing and definition of employment, the roles of split-ups and mergers, and the relative magnitudes of rehiring and new hiring and of quits and layoffs – and they contain a rich set of firm characteristics that may affect job and worker turnover. The results imply that job destruction and worker separation rates in industrial firms rose in the early 1990s, as did job flows as a fraction of worker flows and layoffs as a fraction of separations. By contrast, job creation and worker hiring rates were flat until 1999, the former low and the latter surprisingly high. Heterogeneity in individual firm behavior increased throughout. New firms and old enterprises that have been reorganized display much larger flows compared with unreorganized enterprises. Unions appear to reduce worker flows, but the structure of neither product nor labor markets shows a significant impact. Private ownership has ambiguous effects: insider ownership, particularly by managers, is associated with higher worker flows and excess job reallocation, while outsider ownership, particularly by blockholders, is associated with lower flow rates. A measure of adjustment costs constructed from the worktime necessary to hire and train a new employee is strongly related to variables usually associated with adjustment costs, including worker wage, education, firm size, capital intensity, and labor productivity, but only weakly to job and worker turnover. Little evidence is found that firms? employment adjustments have become more sensitive to adjustment costs during the transition, but worker and manager ownership are associated with more sensitivity than are other types of ownership.
Keywords: E24; P23; J63; J23; P31; 330; job creation; job destruction; labor turnover; layoffs; transition; Russia; Industrielle Beschäftigung; Strukturwandel; Arbeitsmobilität; Personalabbau; Arbeitsnachfrage; Übergangswirtschaft; Rußland